Patient Satisfaction about Nurse Caring Behavior: Based on Swanson’s Theory of Caring and Transcultural Nursing Theory - Ellina, Agusta Dian; Nursalam, Nursalam; Yunitasari, Esti; Rusmawati, Aprin (International Journal of Psychosocial Rehabilitation, 2020)
Caring is one of the main ways to get patient satisfaction. However, caring has only been interpreted as empathy, and without regard to the cultural background of patients. The aim of this study was to assess patient satisfaction about nurse caring behavior and to identify the predictors based on Swanson’s Theory of Caring and Transcultural Nursing Theory. Method: Cross-sectional studies were conducted in patients at a hospital in Gresik District (n = 520 by simple random sampling) from August to December 2019. This study used maintaining beliefs, culture care preservation, knowing, being with, negotiating, doing for, enabling, and restructuring as independent variables, and patient satisfaction as the dependent variable. The instrument in this study was developed in accordance with the standard guideline of Swanson’s Theory combined with Transcultural Nursing Theory; patient satisfaction was measured using PSQ. Multiple linear regression was used to identify predictors. Result: Mean score of patient satisfaction was 7.09 (SD = 0.936), maintaining belief (0,02), culture care preservation (0.03), knowing (0.01), being with (0.03), negotiation (0.02), doing for (0.03), enabling (0.04), and restructuring (0.03) significantly predicted client satisfaction (R Square = 0.895). The constructs of the Cultural Caring Model significantly predicted patient satisfaction. This study supports an investigation about the factors underlying client satisfaction on a larger scale, as well as the identification of targets in designing future interventions.